AI for diversity - Søraa, Roger Andre (Boca Raton, FL : CRC Press, 2023)
"Artificial Intelligence (AI) is increasingly impacting many aspects of people's lives across the globe, from relatively mundane technology to more advanced digital systems which can make their own decisions. While AI has great potential, it also holds great peril depending on how it is designed and used. AI for Diversity questions how AI technology can lead to inclusion or exclusion for diverse groups of society. The way data is selected, trained, used, and embedded into societies can have unfortunate consequences unless we critically investigate the dangers of systems left unchecked, and can lead to misogynist, homophobic, racist, ageist, transphobic or ableist outcomes. This book enables the reader to step back and see how AI is impacting diversity in humans impacted by AI and how diversity-awareness strategies can impact AI. Dr. Roger A. Søraa is an Associate Professor at the Department of Interdisciplinary Studies of Culture at NTNU Norwegian University of Science and Technology. His main research interests are the digitalization and robotization of society and the ethical, gendered, and epistemological consequences of this. Dr. Søraa leads the Digitalization and Robotization of Society research group and coordinates several research projects, including the Horizon Europe project "BIAS: Mitigating Diversity Biases in the Labor Market.""-- "Artificial Intelligence (AI) is increasingly impacting many aspects of people's lives across the globe, from relatively mundane technology to more advanced digital systems which can make their own decisions. While AI has great potential, it also holds great peril depending on how it is designed and used. AI for Diversity questions how AI technology can lead to inclusion or exclusion for diverse groups of society. The way data is selected, trained, used, and embedded into societies can have unfortunate consequences unless we critically investigate the dangers of systems left unchecked, and can lead to misogynist, homophobic, racist, ageist, transphobic or ableist outcomes. This book enables the reader to step back and see how AI is impacting diversity in humans impacted by AI and how diversity-awareness strategies can impact AI. Dr. Roger A. Søraa is an Associate Professor at the Department of Interdisciplinary Studies of Culture at NTNU Norwegian University of Science and Technology. His main research interests are the digitalization and robotization of society and the ethical, gendered, and epistemological consequences of this. Dr. Søraa leads the Digitalization and Robotization of Society research group and coordinates several research projects, including the Horizon Europe project "BIAS: Mitigating Diversity Biases in the Labor Market.""--